Penggunaan Biochar untuk Meningkatkan Kualitas Tanah pada Sistem Pertanian Berkelanjutan - Tuti Ariani Bawamenewi; Friska Hastika Gea; Septenius Waruwu (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research is about the influence of biochar, a carbon-rich material from biomass pyrolysis, on soil quality in a sustainable agricultural system. Biochar plays an important role in increasing soil organic content, improving soil structure, increasing crop productivity, and reducing greenhouse gas emissions. Research results show that biochar application can increase air and nutrient retention, improve soil biological activity, and reduce dependence on chemical fertilizers. In addition, biochar contributes to climate change mitigation through carbon storage and reduces dependence on chemical fertilizers. Thus, biochar has great potential as an innovative solution to support productive and environmentally friendly agriculture. Biochar also helps to create a more productive and environmentally friendly farming system, making it relevant as an innovative solution in supporting agriculture.